NATURE, DEMOGRAPHICS, AND FREQUENCY OF SUICIDE INCIDENTS IN THE NSUKKA UNIVERSITY COMMUNITY - Ngwu, Judith Kelechi; Nwakozo, Nonye Chineme; Okorie, Chinyere Juliet; Nwokeoma, B N (International Journal of Allied Research in Sociology and Anthropology, 2024)
This study titled "Assessment of Social and Cultural Factors Predisposing Individuals to Suicide in the Nsukka University Community" examines the complex interplay of sociocultural dynamics contributing to suicidal behavior among students at the University of Nigeria Nsukka (UNN). Suicide, a significant global public health issue, is particularly critical in university environments due to the unique pressures faced by students. This research addresses a gap in existing studies by focusing specifically on the Nigerian university context. Employing a cross-sectional survey design, the study gathered quantitative data from 611 respondents through a multi-stage sampling technique and qualitative data from in-depth interviews with university staff. The findings reveal that relationship breakups (30.6%), loss of loved ones (30.4%), and social stigma (18.1%) are prominent social factors predisposing individuals to suicide in the Nsukka community. Cultural stigma and religious beliefs significantly deter individuals from seeking help, exacerbating feelings of isolation and hopelessness. The study also highlights the profound emotional and social impacts of suicide, including anger (57.3%), depression (36.8%), and social withdrawal among the victim's close associates. Female freshmen and male senior students are identified as the most common victims, influenced by factors such as poor communication, sexual abuse, and academic stress. The research underscores the need for targeted interventions, recommending the establishment of comprehensive mental health services, educational programs to reduce cultural and religious stigma, and the integration of stress management training into the university curriculum. These measures aim to address the specific challenges faced by the Nsukka University community, ultimately contributing to the prevention of suicide and the improvement of student well-being.